Indonesia’s Digital Financial and Economic Transformation Through Digitalize Redenomination - Silvia Puspa Kumaeroh; Muhammad Ayesha Arif Sandy; Muhammad Ikhwanurrohiim Septenta; Fina Dwi Utami; Mutiara Tresna Parasetya (Universitas Sebelas Maret, 2021)
The financial sector plays an important role in the economy and continues to develop. Some central banks are actively exploring the initiation of digital currency that will become a legal tender [6]. This digital currency is known as the Central Bank Digital Currency (CBDC). Apart from the technological aspect, the CBDC must also be supported by the efficient value of the rupiah denomination. Therefore, it is necessary to simplify the number of digits in the rupiah denomination with a redenomination policy. The implementation of the two policies separately will take a long time in the formulation process. This research comes up with a new concept called